Intra-arterial Chemotherapy for Malignant Tumors of Head and Neck Region Using Three Types of Modified Injection Method - Kumagai, T. (Centauro S.r.l., 2003)
Relatively higher infusion rate in the intra-arterial chemotherapy (IA chemotherapy) could induce the higher concentration and the more sufficient distribution of chemotherapeutic agents on tumors. To get the relatively higher infusion rate in IA chemotherapy, we used three types of injection method: high-flow injection, high-dose injection with detoxification and flow-controlled injection method for the treatment of malignant brain tumors, skull base tumors and head and neck tumors. Between January 1997 and October 2001, twenty-seven patients (mean age 61 y.o.) with supratentorial glioblastoma (4 cases), supratentorial anaplastic astrocytoma (1), CNS lymphoma (2), matastatic skull base tumors (3), and neck tumors (15 squamous cell carcinoma, 1 malignant melanoma and 1 neuroblastoma) received our three types of IA chemotherapy. Sixty-five consecutive procedures were performed. Conventional radiation therapy and/or surgical removal were performed in some of these patients. The median follow-up period was 10 months ranging 2 to 56 months. Fifteen (55.6%) and 6 (22.2%) of 27patients achieved complete response (CR) and partial response (PR) respectively after initial treatment [CR+PR: 21 (77.8%)]. All responded patients showed clinical improvement. The response rate declined to 55.6% at the end of follow-up period. Eighteen patients are still alive and 15 of them show no evidence of local recurrence. The median post treatment survival was 12 months. There was no serious complication except transient nausea in 4 of 27 (14%) patients, vertigo and granulocytopenia in 1 each (3%) of 27 patients. Our modified IA chemotherapy has provided favorable clinical and radiological results without technical difficulties and serious complications.